O etnoconhecimento do povo Pykahu (Parintintin): a utilização de plantas e outros meios no processo de restabelecimento da saúde - Juliano Strachulski; Nicolas Floriani; Adnilson de Almeida Silva; Luís Carlos Maretto; Severino Parintintin (Confins)
The article seeks to analyze how the Parintintin people called Pykahu, from the Aldeia Traíra, in the Terra Indígena Nove de Janeiro, in the municipality of Humaitá – Amazonas state, establish the process of restoring health through their ethno-knowledge. For this, they build the relationship as a result of their spatial experiences since immemorial time so that they use plant and animal species, in addition to minerals, which in their conceptions have healing powers in the physical body and in the spirit. As a method, it is based on empiricism and oral reports produced by Parintintin, in addition to using the “snowball” technique to obtain results. These reflect ethno-knowledge with respective uses to obtain health and are linked to social, cultural and spiritual activities.